Teachers shape secondary school students' behaviours through the use of learning theories: the case of Malaysia - Mohd Jelani, Nurul Syazana; Salim, Siti Suria; Zaremohzzabieh, Zeinab (Global Academic Excellence, 2021)
The aim of this study is to explore the understanding and the application of learning theories among the teacher in shaping students’ behaviour. In-depth one-to-one interviews with five experienced teachers were carried out to collect the data. Collected data were analysed based on a qualitative approach by using John Hattie’s eight-mind frame in order to build consistent data. Two themes and twelve sub-themes emerged from the interviews, including mindset (mind-frame 1 to 8) and practices (punishments, rewards, approaches the students, and way of thinking). The findings demonstrated that while teachers' perspectives on learning theories varied, they are largely consistent with Hattie’s mind frame. When perceptions and beliefs are shared, Hattie's mind frames may prove the way of thinking, and it can identify a successful teacher's style of thinking. Learning theories are important for students' learning, according to the teachers in our study, however, it depends on the practices and how the teachers apply the practices in learning theories. Going forward, this research adds to the moulding of school students' behaviours by allowing teachers to use these learning theories in a novel method that could become a new teaching practice in the school system.